"Quality" in urban management - Van Amsterdam, Errol Ernest (Department of Civil Engineering, 2016)
This Paper brings two important and related issues of current and topical interest together, and argues that this provides an important element that is currently lacking in the urban management framework. It does this through the application of what until relatively recent times in even the advanced industrial economies, was seen as a tool of efficiency enhancement in the production of goods. Quality Assurance and Management concepts are now firmly entrenched in the corporate approach to the more efficient production of both goods and services. Herein lies the justification for the line pursued in the pages which follow. The city role, as described, includes to a significant degree, the provision of space for accommodating economic activities. But through the city's role in administering, in promoting and controlling change, and in providing and distributing services which the community has determined to exercise control over itself, City Management impacts directly on the efficiency of all activities taking place within city limits.